Catholic Schools and the Immigrant Community: A Look Backward and Forward - Collins, F.S.C., Michael (Catholic Education: A Journal of Inquiry and Practice, 2010)
Michael Collins, F.S.C., Ed.D. is a member of the Brothers of the Christian Schools, or Christian Brothers. He currently serves as the president of his alma mater, DeLa Salle High School, in Minneapolis, Minnesota. In 2007 Br. Collins received the National Catholic Educational Association Sr. Catherine McNamee Award for outstanding leadership in diversity. What follows is Br. Collins’s address to attendees at the first Catholic Higher Education Collaborative conference (CHEC), held at Loyola Marymount University (LMU) in January 2009. In his address, Br. Collins recounts instances of racism and prejudice in his years as a student and later teacher and administrator in Catholic schools. He expands the notion of immigrant to include those brought to this country by force. He maintains that Catholic educators have an obligation to welcome and assimilate those who find themselves in a new place regardless of circumstance.